(untitled) (Research, Society and Development, 2020)
The aim of this study is to explore the acquisition of competencies of community health agents (CHA) in the face of congenital syphilis. Bibliographic research, carried out in the Virtual Health Library having as inclusion criteria studies available entirely on the Internet, independent of languages and time space, which include the work of the community health agent involved with the suspicion or diagnosis of congenital syphilis and publications that explore the competencies of the CHA. We selected 13 articles and 8 publications from the Ministry of Health. The study brought an international view of the work of the CHA from the formulation of the categories of analysis: General characteristics of cha; The home visit as a key competence of the CHA; Competencies of CHA in relation to congenital syphilis; Salary remuneration of the CHA; The competencies of the CHA before the SUS and training of the CHA for the acquisition of competencies. This professional has not yet been perceived as a possible catalyst link of results also in the problem of congenital syphilis. It is concluded that the nursing professional needs to be visionary about the health of the population, the economy of the System referring to avoidable treatments, the preventable risks in health and the quality of care based on simple and low-cost strategies, such as the training of CHA, respecting their academic level, their workload, and, above all, their competencies predetermined by the Ministry of Health. The investment in new publications with this theme would expands the knowledge of the work of a professional who is the link between the community and the health service.